Never-ending story. (Economist, 2017)
The article discusses the allegation against Russia for effecting the 2016 U.S. Presidential elections for hacking the emails of political party Democratic. It mentions an investigation carried out by Devin Nunes, chairman of the U.S. House Intelligence Committee, according to which someone from Trump's campaign may have co-ordinated with Russia.